Expression of CD7, CD20 and CDX-2 in a Secondary Signet-Ring Cell Tumor of the Prostate: A Case Report. (January 2013) - Cimino, S.; Russo, G.I.; Favilla, V.; Fragalà, E.; Collura, Z.; Zanghì, A.; Castelli, T.; Madonia, M.; Morgia, G.
As is well-known, signet ring cell carcinoma (SRCC) rarely appears as a histological finding in the prostatic tissue. Nevertheless, a differentiation should be made between a primary tumor and a metastatic disease. We describe the case of a 52-year-old man with lower urinary tract symptoms, serum total PSA of 0.2 ng/ml, elevated serum CEA and CA19-9 levels. Two years prior to presentation, he underwent total gastrectomy with histological findings indicating "poor differentiated adenocarcinoma with signet-ring cell". A palpable nodule was found on digital rectal examination and for this reason he underwent 12-core transperineal prostate biopsy with a diagnosis of "poor differentiated adenocarcinoma with signet-ring cell and adipose tissue infiltration". Immunohistochemical examinations revealed positivity for PAS, CK7 and CDX-2, focal positivity for CK20 and negativity for PSA and PSAP. The diagnosis of a prostatic secondary SRCC was possible given the positivity to CK7, CDX-2, focal positivity to CK20 and negativity to PSA.